A method to determine agro-climatic zones based on correlation and cluster analyses - Borges Valeriano, Taynara Tuany [UNESP]; de Souza Rolim, Glauco [UNESP]; de Oliveira Aparecido, Lucas Eduardo [UNESP] (Springer Nature, 2017)
Determining agro-climatic zones (ACZs) is traditionally made by cross-comparing meteorological elements such as air temperature, rainfall, and water deficit (DEF). This study proposes a new method based on correlations between monthly DEFs during the crop cycle and annual yield and performs a multivariate cluster analysis on these correlations. This ‘correlation method’ was applied to all municipalities in the state of São Paulo to determine ACZs for coffee plantations. A traditional ACZ method for coffee, which is based on temperature and DEF ranges (Evangelista et al.; RBEAA, 6:445–452, 2002), was applied to the study area to compare against the correlation method. The traditional ACZ classified the “Alta Mogina,” “Média Mogiana,” and “Garça and Marília” regions as traditional coffee regions that were either suitable or even restricted for coffee plantations. These traditional regions have produced coffee since 1800 and should not be classified as restricted. The correlation method classified those areas as high-producing regions and expanded them into other areas. The proposed method is innovative, because it is more detailed than common ACZ methods. Each developmental crop phase was analyzed based on correlations between the monthly DEF and yield, improving the importance of crop physiology in relation to climate.
Keywords: Coffee; Crop zoning; Multivariate analysis; Water deficit